Penggunaan Differential Thermal Analysis (DTA) Pada Penentuan Aktivitas Dan Reaktivitas Katalis Fe2O3, Co3O4, NiO, CuO, dan LaMO3 (M=Fe, Co, dan Ni) Untuk Oksidasi CO Menjadi CO2 - Djulia Onggo; Hamzah Fauzi (Institut Teknologi Bandung, 1999)
The catalyst activity of Fe2O3, Co3O4, NiO, CuO, and LaMO3 (M = Fe, Co, and Ni) has been determined using Differential Thermal analysis apparatus. The increased temperature rate has been used at 25oC per min. in the atmosphere of 40% CO, 40% N2 and 20% O2. Mixture gases. The analysis result shows that the order of catalytic activity is Co3O4 > CuO > Fe2O3 > NiO > LaCoO3 > LaFeO3 > LaNiO3. Beside of catalytic activity, this method can be used to determine the starting temperature of carbon monoxide oxidation reaction, which refer to the catalytic reactivity. The order of catalytic reactivity is Co3O4 > CuO > NiO > Fe2O3 > LaCoO3 > LaNiO3 > LaFeO3.